ANXA6 Contributes to Radioresistance by Promoting Autophagy via Inhibiting the PI3K/AKT/mTOR Signaling Pathway in Nasopharyngeal Carcinoma - Chen, Qianping; Zheng, Wang; Zhu, Lin; Yao, Dan; Wang, Chen; Song, Yimeng; Hu, Songling; Liu, Hongxia; Bai, Yang; Pan, Yan; Zhang, Jianghong; Guan, Jian; et al. (Frontiers in Cell and Developmental Biology, 2020)
Radiotherapy is a conventional and effective treatment method for nasopharyngeal carcinoma (NPC) although the residual and recurrent tumors due to radioresistance are the main reasons for the failure of radiotherapy. However, the mechanism and predictive marker of NPC radioresistance are still obscure. In this study, we identified Annexin A6 (ANXA6) as a candidate of radioresistance marker by using Tandem Mass Tag quantitative proteomic analysis of NPC cells and gene chip analysis of NPC clinical samples with different radiosensitivity. It was observed that the high expression level of ANXA6 was positively correlated with radioresistance of NPC, and inhibition ANXA6 by siRNA increased the radiosensitivity. The incidence of autophagy was enhanced in the established radioresistant NPC cells in comparison with its parent cells, and silencing autophagy by LC3 siRNA (siLC3) sensitized NPC cells to irradiation. Furthermore, ANXA6 siRNA (siANXA6) suppressed cellular autophagy by activating PI3K/AKT/mTOR pathway, leading to radiosensitization ultimately. Combination of siANXA6 and CAL101 (an inhibitor of PI3K, p-AKT and mTOR concurrently) significantly reversed the above siANAX6-reduced autophagy. Suppression of PI3K/AKT/mTOR by CAL101 also increased the expression of ANXA6 in the manner of a negative feedback. In conclusion, this study revealed for the first time that ANXA6 could promote autophagy by inhibiting PI3K/AKT/mTOR pathway and thus contributes to radioresistance of NPC. In significance, ANXA6 might be applied as a new predictive biomarker of NPC prognosis after radiotherapy.